Reagent approaches for improved detection of chlorate and perchlorate salts via thermal desorption and ionization. (13th December 2015) - Kelley, Jude A.; Ostrinskaya, Alla; Geurtsen, Geoff; Kunz, Roderick R.
Abstract : Rationale: Techniques for improving the detectability of chlorate and perchlorate salts with thermal desorption based ionizers (i.e. radioactive, corona discharge and photoionization‐based) are desired. This work employs acidic reagents to chemically transform chlorate and perchlorate anions into traces of chloric and perchloric acid. These high vapor pressure acids are easier to detect than the originating salts. Methods: The efficacy of the reagent chemistry was quantified with a triple‐quadrupole mass spectrometer interfaced with a custom‐built thermal‐desorption atmospheric‐pressure chemical ionization (TD‐APCI) source. Additional experiments were conducted using tandem IMS/MS instrumentation. Reagent pKa and pH values were varied in order to gain a better understanding of how those parameters affect the degree of observed signal enhancement. Results: Samples of chlorates and perchlorates treated with liquid acidic reagents exhibit signal enhancement of up to six orders of magnitude compared with signals from untreated analytes. Three orders of magnitude of signal enhancement are demonstrated using solid‐state reagents, such as weakly acidic salts and polymeric acids. Data is presented that demonstrates the compatibility of the solid‐state approach with both MS and IMS/MS platforms. Conclusions: Several methods of acidification were demonstrated for enhanced vaporization and detection of chlorates and perchlorates. For applications where rapid surface collection and analysis for chlorates and perchlorates are desired, the solid‐state approaches offer the simplest means to integrate the reagent chemistry into MS or IMS detection. Copyright © 2015 John Wiley & Sons, Ltd.